Healing potential of art therapy: a narrative review of neuro-psycho-cultural mechanisms in mental health - He, Jiarong; Zhang, Zhengyi (Frontiers in Psychology, 2026)
IntroductionArt therapy (AT) is a non-pharmacological complementary intervention that integrates biological, psychological, and cultural dimensions of healing through creative expression. This narrative review aims to synthesize the historical evolution, theoretical foundations, and clinical applications of AT, proposing a neuro-psycho-cultural framework to elucidate its therapeutic mechanisms.MethodsWe conducted a purposive literature search in PubMed, Web of Science, and PsycINFO (1990-2025) using keywords such as “art therapy,” “neuroaesthetics,” “default mode network,” and “interpersonal neural synchrony”, etc. Studies were selected based on their relevance to constructing a neuro-psycho-cultural model of AT.ResultsAT facilitates healing through multiple mechanisms: (1) neurobiologically reconfiguring the default mode network (DMN), salience (SEN), and central executive networks (CEN), enhancing interpersonal neural synchrony (INS), and modulating biomarkers; (2) psychologically fostering self-identity, emotion regulation, and flow states; (3) culturally, adaptive frameworks that validate its transcultural applicability. Clinical applications demonstrate AT's benefits in trauma, schizophrenia, neurodegenerative diseases, and cancer-related symptoms.DiscussionThe neuro-psycho-cultural framework positions AT as an integrative, patient-centered intervention that bridges neuroscience, psychology, and cultural anthropology. Despite promising evidence, future research should prioritize rigorous controlled trials, standardized outcome measures, and cross-cultural validation to fully establish AT's efficacy and mechanisms.